Laboratory findings in COVID-19 diagnosis and prognosis (2020)
Background: Since its first description, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), formerly known as 2019- nCoV, has attracted tremendous attention in a short period of time as the death toll and number of confirmed cases grows unceasingly. Methods: To provide a better understanding of the importance of abnormal laboratory findings in COVID-19 diagnosis and prognosis, we searched the Scopus, PubMed, and Web of Science medical databases and selected 19 articles (totaling 2,988 patients, 484 of whom [16.1%] had severe disease) that reported panels of laboratory examinations in patients with COVID-19. Results: Although in vitro diagnostics, primarily using PCR- and ELISA-based methods, efficiently contribute to the etiological identification of SARS-CoV-2 infection, we suggest that laboratory medicine may also be of significant assistance when differentiating between severe and non-severe COVID-19. Conclusion: When we wrote this article, our ability to provide a definitive conclusion may have been adversely affected by some limitations, such as the low sample size, differently applied methods, dissimilar reference ranges, non-synchronized representations of results, and variety of the patients’ panels. Despite the limitations, the analysis of the current scientific literature demonstrates the value of laboratory parameters as simple, rapid, and cost-effective biomarkers in COVID-19 patients